Problem Diagnosis dan Tatalaksana Pasien Syok Sepsis dengan Meningitis Suis - I Made Dedy Kusnawan (Jurnal Medika Hutama, 2023)
Sepsis is a condition of clinical syndrome that occurs due to excessive body response to an infection that includes inflammatory, autoimmune, and coagulation processes. Sepsis treatment requires a quick diagnosis and appropriate therapy to reduce mortality caused by this condition. This case report aims to provide an overview of diagnostic and management shock sepsis. A 43-year-old male patient came from refferal from private hospital to emergency ward with diagnostic dengue shock syndrome. Patient came with chief complaint of decrease of consciousness since sunday afternoon. Firstly, the patient can still do communication. however, after some time, the patient cannot be communicated and looks agitated. Physical examination found tightness (respiration rate 26 times/ minute), blood pressure 100/70 mmHg, 89 % saturation via nonoxygen rebreathing mask 15 liters per minute, pulse 106 times per minute, GCS E3V3M5, temperature 38,4 ºC. Both sclerae appear to have icterus, from a physical examination found nuchal rigidity, cold in distal extremity. Through an examination of complete blood count found leukocytosis (36,1 x 103/µL) with predominant neutrofil (33,9 x 103/µL). From liver function examination found an increase in SGOT (224.5 mg/dl) and SGPT (165.2 mg/dl). Renal function examination was found to increase in urea (27,1 mg/dl) and creatinine (3mg/dl). SOFA score this patient is 13 point, criteria to identify sepsis. Treatment of sepsis must be based on rapid diagnosis and appropriate resuscitation treatment to reduce mortality caused by sepsis.